Damage detection in CFRP by coupling acoustic emission and infrared thermography. (February 2016) - Munoz, V.; Valès, B.; Perrin, M.; Pastor, M.L.; Welemane, H.; Cantarel, A.; Karama, M.
Abstract: Acoustic emission (AE) and infrared thermography (IT) are simultaneously combined to identify damage evolution in carbon fibre reinforced composites. Samples are subjected to tensile static loads while acoustic emission sensors and an infrared camera record the acoustic signals and the temperature variations respectively. Unsupervised pattern recognition procedure is applied to identify damage mechanisms from acoustic signals. Thermodynamic arguments are introduced to estimate global heat source fields from thermal measurements and anisotropic heat conduction behavior is taken into account by means of homogenization technique. A spatial and time analysis of acoustic events and heat sources is developed and some correlation range in the AE and IT events amplitude are identified.